PENGUATAN KARAKTERISTIK DAN KOMPETENSI KEWIRAUSAHAAN UNTUK MENINGKATKAN KINEERJA UMKM DI KABUPATEN SERANG - M. Ilmi Syiraf; Syamsul Hidayat (Universitas Bina Bangsa, 2022)
Entrepreneurial characteristics and competencies are two important factors needed by entrepreneur Micro, Small and Medium Enterprises (SMEs) to face the environmental challenges in the dynamic world of business and achieve high business performance. This study aimed to examine the effect of the entrepreneurial characteristics and entrepreneurial competencieson SMEs performance. The study was conducted on SMEs in Serang. The research sample is 69 SMEs were determined through purposive sampling method. Data were collected through a survey with questionnaires. Data were analyzed using structural equation modeling with Partial Least Square (PLS) approach. The results showed that entrepreneurial characteristics have significant positive effect on entrepreneurial competencies, but entrepreneurial characteristics have not significant effect on the SMEs performance and entrepreneurial competencies have significant positive effect on the performance of SMEs. The results also indicate that entrepreneurial competence full mediation the relationship between entrepreneurial characteristics and SMEs performance.